2000
DOI: 10.1016/s0886-3350(00)00432-6
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green staining in traumatic cataract

Abstract: We report the first case of indocyanine green (ICG) being used in an eye with an anterior capsule that was not completely intact. We found that ICG seems to have a selective affinity for the anterior capsule over cortical lens material. The patient had a corneal perforation with a wire and developed endophthalmitis requiring pars plana vitrectomy with intravitreal antibiotics. He subsequently developed a white traumatic cataract with an anterior capsule tear. Five months after the injury, he had cataract extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…1 It can be particularly useful in eyes with traumatic capsule tears. 19 Other agents, including trypan blue and gentian violet, are also useful for capsule visualization. 20 Studies show that trypan blue is less toxic than ICG to the RPE.…”
Section: Discussionmentioning
confidence: 99%
“…1 It can be particularly useful in eyes with traumatic capsule tears. 19 Other agents, including trypan blue and gentian violet, are also useful for capsule visualization. 20 Studies show that trypan blue is less toxic than ICG to the RPE.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]14 Recently, use of this dye to delineate the internal limiting membrane and epiretinal membrane during retinal surgery has been reported. 25,26 Although in previous reports of ICG for cataract surgery the concentration of dye used was 8 Pandey et al, 6 Bhartiya et al, 15 Sharma and coauthors, 20 0.50%, [5][6][7]14,17,18 in our study we found satisfactory staining with ICG 0.25%. In the first part of our study, 21 we found that exposure to ICG 0.50%, but not ICG 0.25%, caused significant corneal endothelial cytotoxicity in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] These dyes have also been found helpful for the following: to ''find'' the leading edge of a ''lost'' capsulorhexis, 13 to visualize the anterior capsule tear in cases of traumatic cataract, 14 to facilitate capsulorhexis during phacoemulsification of corneal opacities, 15 to facilitate removal of posterior capsule plaque after cataract surgery or assist in posterior CCC in children, [16][17][18] and to assist in training surgeons in phacoemulsification techniques. 19,20 Indocyanine green (ICG), trypan blue (TB), and fluorescein sodium (FS) have been used most widely for the purposes described.…”
mentioning
confidence: 99%
“…Different methodologies for injecting the dye have been described, including beneath air [1,2,6,12,[17][18][19][20][21][22][23][24], and in balanced salt solution (BSS) [16], beneath ophthalmic viscosurgical device (OVD) [5,17,[25][26][27][28], beneath OVD and BSS [29,30] and mixing with an OVD [31][32][33]. Wong et al [14] compared the safety and effectiveness of Trypan Blue staining under either air or viscoelastic and found both methods equivalent.…”
Section: Review Of Recent Studiesmentioning
confidence: 99%